The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1167/iovs.16-20336
|View full text |Cite
|
Sign up to set email alerts
|

Myocilin Regulates Metalloprotease 2 Activity Through Interaction With TIMP3

Abstract: PurposeTo elucidate functions of wild-type myocilin, a secreted glycoprotein associated with glaucoma.MethodsLysates of mouse eyes were used for immunoprecipitation with affinity-purified antibodies against mouse myocilin. Shotgun proteomic analysis was used for the identification of proteins interacting with myocilin. Colocalization of myocilin and tissue inhibitor of metalloproteinases 3 (TIMP3) in different eye structures was investigated by a multiplex fluorescent in situ hybridization and immunofluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Insufficient myocilin in Dupuytren's tissue may therefore promote pro-fibrotic Wnt signalling. TIMP3 has been shown to interact with myocilin to regulate MMP2 activity (Joe et al, 2017) and a dearth of myocilin in Dupuytren's tissue may result in a corresponding increase in MMP2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient myocilin in Dupuytren's tissue may therefore promote pro-fibrotic Wnt signalling. TIMP3 has been shown to interact with myocilin to regulate MMP2 activity (Joe et al, 2017) and a dearth of myocilin in Dupuytren's tissue may result in a corresponding increase in MMP2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the physiological function of the intracellular proteolytic processing of myocilin remains unknown, the amount of proteolytic myocilin may be associated with the regulation of the normal TM structure through extracellular proteins, including fibrillin-1 (45), secreted protein acidic and rich in cysteine (SPARC) (34), hevin (34,46), collagen (45), optimedin (47), decorin (45), fibronectin (48) and laminin (45,49), which contribute to the regulation of aqueous humor outflow that can affect IOP (23). The identification of proteins interacting with myocilin is a possible approach to elucidating its functions, since interacting proteins are typically involved in the same physiological and pathological processes (50).…”
Section: Physiological Functions and Characteristics Of Myocilinmentioning
confidence: 99%
“…Recently, the crystal structure of myocilin-OLF was elucidated, and it indicated that myocilin-OLF belongs to the five-bladed β-propeller family (108), which is a known hub for protein-protein interactions. To date, a number of extracellular proteins interacting with myocilin have been identified, including tissue inhibitor of matrix metalloproteinase (TIMP3) (8,50), fibronectin (107), flotillin-1 (109) and hevin (46).…”
Section: Imbalance Of Pathogenic Myocilin and Extracellular Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Investigative Ophthalmology & Visual Science , Joe et al . 3 report use of a shotgun proteomic approach for discovery of new MYOC interacting partners. They identify TIMP3 as the third MYOC OLF binding protein.…”
mentioning
confidence: 99%